Going Global: Considerations and Challenges in Designing a ’Global’ MBA - Robinson, Sarah; Ramanau, Ruslan; Reid, Kristen; Honnor, Keith (Proceedings of the International Conference on Networked Learning, 2010)
Addressing the theme of globalisation and interculturality in networked learning, this poster focuses on the development of a ‘Global’ MBA programme at the Open University Business School (UK), which replaces its existing programme, starting 2010. The poster presents an in-depth reflective account of the process of redesigning the first (foundation) course in this programme, highlighting the challenges encountered during the design process in areas of technology, delivery, support, pedagogy and organisational culture. It presents the important questions addressed by the design team, the team’s responses and some of the ways forward considered in the process of developing a primarily on-line model with potential global reach. This work is underpinned by the assumption that the face of distance education is rapidly changing. Online courses that were designed with a view of the Web as primarily a repository of learning resources and a platform for online lectures are giving way to new models of teaching and learning that build on the educational potential of Web 2.0 and other emerging technologies (Anderson 2008). We argue that processes of globalisation both call for and support changes in the ethos of distance education from being primarily focused on delivering content to learners to enabling satisfying cross-cultural learning experiences that necessitate changes to modes of working and collaborating at various levels. This poster therefore presents and explores both barriers to and opportunities for innovation encountered in designing one such course, but which may have wider relevance to the design of technology-enhanced learning experiences in other settings and contexts.